Prevalence of microsporidia in an indigenous Orang Asli community in Pahang, Malaysia - Lono, A.; Kumar, G.S.; Chye, T.T. (2010)
Microsporidia are ubiquitous parasites thought to be closely related to fungi. Their presence in the environment means that humans are frequently exposed to infection. Stool samples were collected from 151 indigenous villagers from the eastern state of Pahang in 2005. The samples were concentrated with water-ether sedimentation, stained with modified trichrome stain and examined under oil-immersion microscopy. Thirty-two specimens (21.2) were positive for microsporidia. Microsporidia were observed as ovoid or rounded ovoid shapes measuring similar to 1 mu m, with a bright pink outline containing a central or posterior vacuole. PCR amplification with specific primers on microscopy-positive specimens amplified Encephalitozoon intestinalis DNA from five of the ten specimens used. (C) 2009 Royal Society of Tropical Medicine and Hygiene. Published by Elsevier Ltd. All rights reserved.